Slow-velocity eccentric-only resistance training improves symptoms of type 2 diabetic mellitus patients by regulating plasma MMP-2 and -9 - Qian, Zhao; Ping, Liu; Dongming, Xu; Xuelin, Zhang (Medicine (Baltimore), 2024)
Objective: This study investigated the intervention effect of slow-velocity eccentric-only resistance training on type 2 diabetic mellitus (T2DM) patients based on the role of matrix metalloproteinase-2 and -9 (MMP-2 and -9) in regulating extracellular matrix homeostasis. Methods: 50 T2DM patients were randomly divided into the slow-velocity eccentric-only resistance training group (E) and control group (C). The E group performed eccentric-only resistance training 3 times a week, every other day for 10 weeks, while the C group did not. Blood samples were collected before and after training, and subjects were tested for changes in clinical parameters, insulin resistance indices [fasting insulin, homeostatic model assessment insulin resistance (HOMA-IR)], MMP-2 and -9, and hydroxyproline, and muscle strength (12-RM), respectively. Results: After 10 weeks of training, the E group showed significant decreases in fasting glucose (P < .05), insulin (P < .05), insulin resistance indices (P < .05), hemoglobin A1c (HbA1c) (P < .01), triglycerides (P = .06) and MMP-2 (P < .05), while total cholesterol (P < .05), MMP-9 (P < .05), hydroxyproline (P < .01), Creatine Kinase (CK) (P < .05), and muscle strength (P < .001) significantly increased. There were no significant changes in the count of neutrophil, lymphocyte and platelet, neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), high-density lipoprotein cholesterol (HDL-c), and low-density lipoprotein cholesterol (LDL-c). Compared with the C group, the E group showed a trend of a significant decrease in triglyceride (P < .05), lymphocyte count (P < .05), fasting glucose (P = .07), and plasma MMP-2 (P < .05), while MMP-9 (P < .05), hydroxyproline (P < .001), and muscle strength (P < .01) significantly increased. However, no significant changes were observed in insulin and insulin resistance indices, HbA1c, total cholesterol, HDL-c, LDL-c, CK, and other inflammatory indicators. Conclusions: Slow-velocity eccentric-only resistance training was beneficial for T2DM, but the potential role of MMP-2 and -9 in regulating extracellular matrix homeostasis is very different in T2DM patients.